Effect of Doxorubicin on Squamous Cell Carcinoma of Skin: Assessment by MRI Relaxometry at 4.7T. (14th September 2019) - Sharma, Ashok; Sharma, Uma; Jagannathan, N. R.; Ray, Ruma; Rajeswari, Moganty Raja
Abstract: Squamous cell carcinoma (SCC) of skin has no standard treatment regimen, resulting in recurrences/metastasis. Although, doxorubicin (Dox), an anthracycline antibiotic has demonstrated some degree of efficacy. Molecular imaging can help in assessment of treatment response and prognosis of SCCs. MRI data showed that spin-spin relaxation (T2) time was longer (138 ± 2 msec) in Dox treated Test-II and there is no significant difference in spin-lattice relaxation (T1) time with respective controls. These findings further corroborated with the histology, proliferation index, apoptotic index, and HMGA1 protein expression. Thus, MRI may be a useful tool for monitoring treatment response noninvasively for skin tumor prognosis.